Sosialisasi Penegakan Undang-Undang No 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup pada Masyarakat di Kecamatan Medan Belawan dan Medan Marelan - MYF Hafidz Nasution; Dwi Sartika Paramyta; Neri Arisuma; Salman Alfarisi; Maya Puspita Ningrum (Universitas Islam Negeri Sumatera Utara, 2022)
AbstractThe activity of PKM is continued from project collaboration of environmental education for water environment improvement in the deli river basin north Sumatra province since 2015 between the University of North Sumatra, University Kitakyushu Japan, and Institute of Graha Kirana. In 2021, this project involves a public in two primary schools, a senior high school dan two junior high schools in Deli River path for more active in conservation environment from Environmental Law knowledge and issue of environmental water (UU No.32 Tahun 2009 and PP No. 22 Tahun 2021). It's expected to lectures who directly involved in this workshop can provide education to the public about Protection and Managing Environment (PPLH) based on UU No 32 Tahun 2009 chapter 1 paragraph 2 that systematic and integrated efforts to preserve function and prevent environmental and/or damage include planning, utilization, controlling, maintenance, supervision, and law enforcement